2013
DOI: 10.1016/j.applanim.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Flooring and driving conditions during road transport influence the behavioural expression of cattle

Abstract: This study examined whether observers could distinguish between cattle that were exposed to various road transport conditions: Experiment 1 compared a manipulated flooring treatment (non-grip flooring, NG) with a control transport event (grip flooring, G) and Experiment 2 compared a manipulated driving style (stop-start driving, SS) with a control transport event of smooth, continuous (C) driving. The behavioural expression of cattle was assessed through the process of Qualitative Behavioural Assessment (QBA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
7
22
1
1
Order By: Relevance
“…One of the findings of present study was that insignificant variation of PCV before, after and after 24h of post transportation also supported by the findings of Stockman et al, 2013). While considering the white blood cell count in current study the TLC was highest after transportation compared to before and 24h of post transportation.…”
Section: Journal Of Animal Health and Productionsupporting
confidence: 77%
See 1 more Smart Citation
“…One of the findings of present study was that insignificant variation of PCV before, after and after 24h of post transportation also supported by the findings of Stockman et al, 2013). While considering the white blood cell count in current study the TLC was highest after transportation compared to before and 24h of post transportation.…”
Section: Journal Of Animal Health and Productionsupporting
confidence: 77%
“…Globally a lots of research have been conducted on transportation stress including Europe (Averós et al, 2008;Averós et al, 2009), United States (Sporer et al, 2007;), Canada (Mitchell et al, 2008, Japan (Ishizaki et al, 2005), Australia (Phillips and Santurtun, 2013;Stockman et al, 2013), UK (Gregory, 2008), Turkey (Teke et al, 2014) Nigeria (Minka and Ayo, 2007;Minka and Ayo, 2013) etc. In transportation the degree of transport stress mostly depends on environmental condition (Aradom, 2013).…”
mentioning
confidence: 99%
“…The results of this study indicate the sensitivity of qualitative behavioural assessment to environmental contexts (in this case the feeding system), therefore making the assessment informative in an integrative sense. Other studies to demonstrate significant treatment differences in QBA scores include studies of sheep and cattle exposed to varying transport conditions (Stockman et al 2011(Stockman et al , 2013Wickham et al 2012), horses before v. after 1 month of intensive handling (Minero et al 2009), or horses filmed at three stages of an endurance ride . These studies also found differences in the animals' affective states between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, assessments may determine if an animal is standing in a relaxed manner or in an alert or focussed manner. Previous QBA studies have shown significant agreement between observers in their assessment of pigs (Wemelsfelder et al 2000Rutherford et al 2012), cattle (Rousing and Wemelsfelder 2006;Brscic et al 2009;Stockman et al 2011Stockman et al , 2012Stockman et al , 2013, buffalo (Napolitano et al 2012), sheep , horses (Napolitano et al 2008;Minero et al 2009;Fleming et al 2013), poultry (Wemelsfelder 2007), and dogs (Walker et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Chulayo et al (2012), Gajana et al (2013), Stockman et al (2013) and Vimiso & Muchenje (2013) emphasized that animals experience stressful conditions in transportation, which negatively affect their welfare and meat quality. Delgado (2003) and Hoffman & Cawthorn (2013) carried out research that was aimed at finding ways of increasing protein sources that would meet all needs since meat is an important constituent of the diet for many consumers.…”
Section: Introductionmentioning
confidence: 99%